ANYONE FOR A GAME OF MONOPOLY™?* A CRITICAL EVALUATION OF THE EVERINCREASING COMMERCIALIZATION OF MAJOR SPORTING EVENTS PART 3: EXAMINING THE LEGITIMACY OF THE CREATION AND MAINTENANCE OF COMMERCIALLY-DRIVEN MONOPOLIES IN SPORTS EVENTS - Andre M Louw (Obiter, 2021)
This is the third and final part in a series of articles which examines the commercial monopoly in a major sports event such as the 2010 FIFA World Cup South Africa, and its protection against ambush marketing by means of (specifically) domestic legislation. This part will continue the evaluation of the role of relevant constitutional guarantees in terms of the South African Bill of Rights, will consider the justification for the protection of commercial rights to such events, will briefly examine recent developments elsewhere in respect of the development of a ‘sports event organiser’s right’, and includes a concluding section with some critical evaluation of the legitimacy of the current state of the law in this regard in South Africa (and elsewhere).